Análise da oferta pública de aquisição de ações e o laudo de avaliação de empresas no Brasil - Medeiros, Luzia Luana da Silva (Universidade Federal Rural do Semi-Árido, 2019)
This research aims to describe characteristics inherent in the notices and appraisal reports of companies used in the Public Tender Offer (OPA) process in Brazil. We analyzed 256 notices and appraisal reports of companies used in OPAs and made available at CVM from 2002 to 2018, resulting in a final sample of 201 companies. Several reasons lead the companies to make the Public Tender Offer, the fund raising and the share control, are very frequent motivations in Brazil. Therefore, the study's main question is raised: what are the relevant characteristics of the appraisal reports of companies and the process of Public Offering for Acquisition of Shares in Brazil? The results indicate that the cancellation of registration and disposal of control purposes are the events that stand out in relation to the others, representing 66.2% and 25.4%, respectively, of the total sample. Among the notices and reports analyzed, it was verified the frequency in which the valuation methods are used to determine the fair value of the company, highlighting that 73.6% corresponds to the use of the CDF method as the main valuation method used by the financial experts. Statistical tests were carried out to evaluate the relevant characteristics of the OPA processes in Brazil. Using a test for Chi-square independence of the variables, it was verified that there is no association between the variables Evaluation Method and Purpose of OPA. We also tested the existence of a time trend in the use of Discounted Cash Flow, within the process of evaluating companies, with a rise in their utilization until the year 2012 followed by a decline until 2018. It was tried to identify which factors influence the motivations and the process of OPA in Brazil, as well as the choice of the company valuation method.
Monografia
Keywords: Avaliação de empresas; Métodos de avaliação de empresas; OPA; Laudo de avaliação; Equity valuation; Methods of valuation; OPA; Appraisal report; ENGENHARIAS::ENGENHARIA DE PRODUCAO